Effect of a single exacerbation on decline in lung function in COPD. (July 2017) - Halpin, David M.G.; Decramer, Marc; Celli, Bartolome R.; Mueller, Achim; Metzdorf, Norbert; Tashkin, Donald P.
Abstract: Background: COPD exacerbations are associated with accelerated lung function decline, but whether they are causal is unknown. We evaluated the effect of a single exacerbation on rate of lung function change using data from the 4-year Understanding Potential Long-term Impacts on Function with Tiotropium (UPLIFT ® ) trial. Methods: Retrospective analysis of annual rates of decline in FEV1 and FVC before and after a single (and the only) moderate-to-severe exacerbation in patients during UPLIFT ® (exacerbator subgroup), compared with changes between the first and second half of the study in a non-exacerbator subgroup. A sensitivity analysis examined annual rates of decline in matched pairs of exacerbators and non-exacerbators. Results: Following the single moderate-to-severe exacerbation, mean annual decline in post-bronchodilator lung function increased compared with the rate of decline before the exacerbation (FEV1 76.5 vs. 39.1 mL/year, p = 0.003; FVC 106.5 vs. 34.7 mL/year, p = 0.011). In non-exacerbators, there were no differences in rates of decline between the first and second halves of the study (post-bronchodilator FEV1 38.2 vs. 41.8 mL/year, FVC 45.3 vs. 43.9 mL/year. Before the single (moderate-to-severe) exacerbation in the exacerbator subgroup, declines in post-bronchodilator FEV1 or FVC were similar to non-exacerbators in the first half of the study; after the single exacerbation they were significantly higher than for non-exacerbators in the second half of the study. The sensitivity analysis showed similar results. Conclusion: A single COPD exacerbation may result in significant increase in the rate of decline in lung function. Highlights: Retrospective analysis of the 4-year UPLIFT ® trial of patients with COPD. Examined the impact of a moderate-to-severe exacerbation on lung function decline. Rate of lung function decline was compared with that of non-exacerbator controls. The rate of decline was significantly increased following a single exacerbation.